2019
DOI: 10.1021/acsami.9b07437
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficiency of InP-Based Red Quantum Dot Light-Emitting Diodes

Abstract: Due to the inherent toxicity of cadmium selenide (CdSe)-based quantum dots (QDs), Cd-free alternatives are being widely investigated. Indium phosphide (InP) QDs have shown great potential as a replacement for CdSe QDs in display applications. However, the performance of InP-based quantum dot light-emitting diodes (QLEDs) is still far behind that of the CdSe-based devices. In this study, we wanted to show the effects of different approaches to improving the performance of InP-based QLED devices. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…The VBM of the thin shell InP QDs was—6.74 eV, which is much lower than most reported green InP QDs (−5.35 eV). [ 31–34 ] The halogen ligand on QD is the main reason for the very low VBM. A similar rule was also mentioned by other studies of PbSe and CdSe QLED that containing Cl − , in which the strong electron negative ligands lower the valence band of QDs.…”
Section: Resultsmentioning
confidence: 99%
“…The VBM of the thin shell InP QDs was—6.74 eV, which is much lower than most reported green InP QDs (−5.35 eV). [ 31–34 ] The halogen ligand on QD is the main reason for the very low VBM. A similar rule was also mentioned by other studies of PbSe and CdSe QLED that containing Cl − , in which the strong electron negative ligands lower the valence band of QDs.…”
Section: Resultsmentioning
confidence: 99%
“…Quantum dot (QD) is the most promising next-generation elements for LED display due to their cost-effective production, superior color purity, nanosecond response time, high quantum yield and precisely tunable emission wavelength through the whole visible to the near infrared range. [1][2][3] Such unique optical properties make QD more suitable to be used as color conversion (CC) than commercial color filter for back light unit, liquid crystal display and LEDs. [4,5] Compare to the conventional phosphors, QD can realizing a wide color gamut due to the narrow emission line width, and a thin light conversion layer to meet the slim criterion of current TVs.…”
Section: Introductionmentioning
confidence: 99%
“…Because InP QDs do not contain heavy metal elements, they show stable quantum yield and size-tunable photoluminescence (PL) emission from visible to nearinfrared (NIR) range, and InP QDs are beneficiary in biological applications. 14,15 For example, Zhang et al carried out in vivo imaging of tumor-bearing nude mice with silica medium composite probe encapsulated InP/ZnS QDs and found that the composite probe had excellent tumor targeting and fluorescence imaging capabilities. 16 More importantly, different from the ionic bond in CdSe QDs, the covalent bond in InP QDs is stronger and more robust, which makes them less toxicity.…”
Section: Introductionmentioning
confidence: 99%